CONSUMER PREFERENCES FOR WARNO TOFU IN AEK PINING VILLAGE, BATANG TORU DISTRICT, SOUTH TAPANULI REGENCY, NORTH SUMATERA - Sri Multiana; Muhammad Authar ND; Hafni Zahara (Jurnal Mahasiswa Agribisnis, 2025)
This research was conducted in Aek Pining Village, Batang Toru District, South Tapanuli Regency, North Sumatra at the Warno Tofu Industry. This study aims to determine what attributes are consumer preferences for Warno Tofu and determine which attributes are most considered by consumers in making purchasing decisions for Warno Tofu. The data used in this study are primary and secondary data. The sampling technique was carried out by chance (accidental sampling). The data analysis methods used are Chi-Square and Multiattribute Fishbein analysis. The results showed that the attributes of tofu that influence consumer preferences in purchasing Warno's Tofu are flavor and durability attributes. It can be seen from the results of the Chi-Square analysis that the taste attribute (0.004) and durability (0.028) have a Sig value < Î± value (0.05), so Ho is accepted, meaning that the taste and durability attributes affect consumer preferences for purchasing Warno Tofu. The attribute of tofu that is most considered in the decision to purchase tofu is the flavor attribute. The order of attributes that become consumer attitudes in purchasing tofu are taste, durability, price, texture and size.